Nanoliposomes Reduce Stroke Injury Following Middle Cerebral Artery Occlusion in Mice. Issue 2 (8th November 2021) - Ahmad, Saif; Truran, Seth; Karamanova, Nina; Kindelin, Adam; Lozoya, Maria; Weissig, Volkmar; Emerson, Hannah; Griffiths, Daniel R.; Vail, Tyler; Lifshitz, Jonathan; Ducruet, Andrew F.; Migrino, Raymond Q.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Neuroprotective strategies for stroke remain inadequate. Nanoliposomes comprised of phosphatidylcholine, cholesterol, and monosialogangliosides (nanoliposomes) induced an antioxidant protective response in endothelial cells exposed to amyloid insults. We tested the hypotheses that nanoliposomes will preserve human neuroblastoma (SH-SY5Y) and human brain microvascular endothelial cells viability following oxygen-glucose deprivation (OGD)–reoxygenation and will reduce injury in mice following middle cerebral artery occlusion. Methods: SH-SY5Y and human brain microvascular endothelial cells were exposed to oxygen-glucose deprivation–reoxygenation (3 hours 0.5%–1% oxygen and glucose-free media followed by 20-hour ambient air/regular media) without or with nanoliposomes (300 µg/mL). Viability was measured (calcein-acetoxymethyl fluorescence) and protein expression of antioxidant proteins HO-1 (heme oxygenase-1), NQO1 (NAD[P]H quinone dehydrogenase 1), and SOD1 (superoxide dismutase 1) were measured by Western blot. C57BL/6J mice were treated with saline (n=8) or nanoliposomes (10 mg/mL lipid, 200 µL, n=7) while undergoing 60-minute middle cerebral artery occlusion followed by reperfusion. Day 2 postinjury neurological impairment score and infarction size were compared. Results: SH-SY5Y and human brain microvascular endothelial cells showed reduced viability post–oxygen-glucose deprivation–reoxygenation that was reversed by nanoliposomes. Nanoliposomes increased protein expressions of HO-1, NQO1 in both cell types and SOD1 in human brain microvascular endothelial cells. Nanoliposomes-treated mice showed reduced neurological impairment and brain infarct size (18.8±2% versus 27.3±2.3%, P =0.017) versus controls. Conclusions: Nanoliposomes reduced stroke injury in mice subjected to middle cerebral artery occlusion likely through induction of an antioxidant protective response. Nanoliposome is a candidate novel agent for stroke.